(untitled) (BioLaw Journal - Rivista di BioDiritto, 2021)
Long-awaited French bioethics reform will constitute a milestone of national legal history. This reform allows all women (single or lesbian couples) to receive medical fertility treatment without any discrimination based on sex or sexual orientation. Moreover, right to know one’s genetic origins is now recognized for donor-conceived people. Nevertheless, many questions are still unsolved, such as rights of persons born through surrogacy or surrogacy for both homosexuals and heterosexuals couples. Even social egg freezing will be legal, but it is not clear how French Healthcare System will respond to the new demands. French bioethics reform is thus thoroughly analized and discussed.